Wood-decay fungi associated with decaying of coarse woody debris in Hail Region, North of Saudi Arabia: Wood-decay fungi in Hail Region, North of Saudi Arabia - Nawaf Alshammari; Alshammari Bader Fraih Z; Al Tami, Mona Saleh; Tarun Kumar Upadhyay (Cellular and Molecular Biology, 2023)
The present study was conducted in order to describe the assemblage of wood decay fungi and mycomycetes associated with the Hail region in the North of Saudi Arabia by using incubation chambers. There was a collection of coarse woody debris from the study area, AL baithe, which was brought to the laboratory and placed inside a series of incubation chambers in which water was added. Over a period of several weeks, fruiting bodies appeared in these chambers which were morphologically analysed via AmScope stereomicroscope and molecular identification was carried out via ITS-1F and ITS-4R DNA sequencing methods. The obtained sequences after successful identification via BLAST analysis were submitted to the Genebank NCBI database. During the course of the study, a total of 20 species of different 14 families of wood-decay fungi were identified of which mycelium has been generated in incubation chambers. Among the identified wood-decay fungi, Phanerochaetaceae (03 species), Bionectriaceae (02 species), Hypocreaceae (02 species) and Chaetomiaceae (02 species) being the most frequent. Hence, the present study was the first one to report on the diversity of wood-decay fungi of Saudi Arabia and was successful in using incubation chambers to describe the specimens of wood-decay fungi associated with coarse wood debris.